Towards sustainable food systems: developing a monitoring framework for the EU - Szvetlana Acs; João Costa Leite; Esther Sanyé-Mengual; Arnaldo Caivano; Rui Catarino; Jean-Noël Druon; Federica Di Marcantonio; Beyhan De Jong; Irene Guerrero; Patricia Gurría; Robert M’barek; Panos Panagos; et al. (Frontiers in Sustainable Food Systems)
Adequate monitoring of the EU transition toward sustainable food systems can promote policy coherence and provide better evidence for informed policy making. This paper presents an initial concept and methodology for an EU food system monitoring framework, integrating a systems’ perspective and key sustainability elements relevant to the EU context. Grounded in scientific evidence and extensive dialogues among scientific experts with interdisciplinary backgrounds, we define an EU food system sustainability model that provides a conceptual framework for monitoring. This model encompasses 12 thematic areas and 37 indicator domains, synthetized through a rigorous review of existing frameworks and the assessment of nearly 250 relevant indicators via a transparent workflow and an integrated collaborative digital tool. We identify data gaps that signal challenges ahead in effective monitoring, but also opportunities for research and cooperation. To advance with an EU food system monitoring framework, it is essential to engage in participatory processes with stakeholders, ensuring an inclusive and transparent approach.